Q: What is the equation for 3 over 2g plus 1 over 6g equals -3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

No. It is a meaningless equation. You may have intended to say: 2 times the sum of x and g is equal to 2x plus 2g.

12g

2g - 9 = -5 Therefore, 2g = 4 Therefore, g = 4/2 g = 2

6g

14g + 7

Related questions

Start with your equation -2g + 11 = -21 Multiply all terms by -1 to get 2g - 11 = 21 Add 11 to both sides to get 2g = 32 Divide both sides by 2 to get g = 16

No. It is a meaningless equation. You may have intended to say: 2 times the sum of x and g is equal to 2x plus 2g.

12g

-3g+6+2g=15 -g=9 g=-9

If: 2g+3 = 4 Then: g = 1/2 or 0.5

27-g = 2g+12 -3g = -15 g = 5

-0.8 or -4/5 is the solution to the equation -2g + 4 + 7g.

2g + 4 - 6 = g + 12g - 2 = g + 12g - g = 1 + 2g = 3Check:2(3) + 4 - 6 = 3 + 16 + 4 - 6 = 44 = 4

2g + 5h

truth or false does 2000mg = 2g

2g + 5g + 14 = 8g + 8 - 3 = 7g +14 = 8g + 5 = 14 - 5 = 8g - 7g so 9 = 1g and therefore g = 9

g equals 9If2g + 14 + 5g = 8g - 3 + 8then:7g + 14 = 8g + 5therefore7g - 8g = -14 + 5-g = -9g = 9.